Programmable Photonic Logic Array Based on Micro-Ring Resonators and All-Optical Modulation - Liu, Jia; Zhou, Shenghang; Sui, Xiubao (Micromachines (Basel), 2025)
All-optical computing is an emerging information processing technology. As a cutting-edge technology in the field of photonics, it effectively leverages the unique advantages of photons to achieve rapid computation. However, the lack of a fully functional and programmable design has slowed the progress of this type of optical computing system, especially in optical logic computing. In this paper, we design and propose a programmable photonic logic array based on all-optical computing methods. By efficiently combining on-chip photonic devices such as micro-ring resonators, we have realized a complete set of reconfigurable all-optical logic computation functions, including basic logic such as IS&NOT, AND, and OR, as well as combined logic, such as XOR and XNOR. To the best of our knowledge, the proposed architecture not only introduces three structurally similar standard logic units but also allows for their multiple-level cascading to form a large-scale photonic logic array, enabling multifunctional logic computation. Furthermore, using two independent wavelengths to represent the high and low levels of logic can effectively reduce cross-talk and overlap between signals, decreasing the dependence on the strength of the optical signal and the decision threshold. Simulation results by Photonic Integrated Circuit Simulator (INTERCONNECT) demonstrate the effectiveness and feasibility of the proposed programmable photonic logic array.